The Effect of Extended Parallel Process Model on Sexual Self- Control of Female Adolescents in Aliabad Kotoul in 2020 - Mahboubeh Tabarsa; Farzaneh Roshangaran; Shahla fakhreazizi; Elham Khaloobagheri; Nafise Hekmati Pour (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: This study we aimed to examine the effect ofExtended Parallel Process Model (EPPM) on thesexual self-control of female adolescents in Aliabad Kotoul in 2020.Methods: This experimental study with two intervention and control groups was conducted on 50 secondyearhigh school female students in Aliabad Katoul, who had been selected by simple random samplingmethod. In the intervention group, 8 training sessions (45-60 minutes each) were carried out in groups of 6-7people, based on the EPPM for 2 months. Data were collected in both groups before and after the intervention,and then were analyzed by SPSS-16 statistical software using descriptive and inferential statistics.Results: Independent t-test did not show a significant difference between the intervention and control groupsbefore the intervention (P = 14.14) in terms of the score of sexual self-control, but after the intervention, itshowed a significant difference (P <0.01) between the two groups. Also, ANCOVA test showed a significantdifference between the two groups by removing the pre-test effect (p <0.01, Eta = 0.64), so that the EPPMwasable to increase the sexual self-control of samples in the intervention group.Conclusion: Considering the effectiveness of EPPM, the results showed that if people understand thatthey are at high risk of disease or health problem, they will be more sensitive towards performing high-riskbehaviors. Therefore, increasing awareness and creating sensitivity can play an important role in controllingbehaviors.